Penerapan Model Pembelajaran Kooperatif Tipe Teams Games Tournament pada Pembelajaran Ekonomi untuk Meningkatkan Motivasi Belajar dan Hasil Belajar Siswa - Natalya Ayu Wardhani, ; Indah Rusminarni, (Pendidikan Ekonomi, 2012)
Recently, the main problem in the formal learning (school) is the low learners absorption. It can be seen trough the low average of students learning outcome. Teachers used to teach the students by the lecture method, thus the students get bored and get the low motivation to study and cant accept the material maximally. The data gathering technique in this study uses the observation sheet of students and teacher activities, students motivation questionnaire, pretest and posttest and documentation. The data analysis of class action research shows that the teachers activities is increased, that is from 79,23% to 90,76%. Students activities are also increase, from 76,67% to 86,67%. The students learning outcome also increase from the classical completeness on the first cycle is 43,58% to 87,5 in the second cycle. Students learning motivation is increased after applying the TGT learning method, that is from 49,84% to 75,26%.